Czuła narracja: nowe oblicze literatury polskiej w oczach Chińczyków - Yinan, Li (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article presents the dynamics, characteristics and the shifting paradigms of the reception of Polish literature in China from 2012 to 2020. The author analyses the reasons for the popularity of the most often translated and read Polish authors on the Chinese publishing market, with particular interest in Czesław Miłosz, Olga Tokarczuk and Andrzej Sapkowski. She also presents the translators – both experienced and often recognised and awarded doyens of Polish studies in China, and those from the intermediate and youngest generations to whom the oldest ones passed the knowledge, skills, passion and the sense of common mission of building cross-cultural dialogue through literature.